2020
DOI: 10.1111/jvec.12377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of boric acid as toxic sugar bait against resistant Aedes aegypti mosquitoes

Abstract: Current methods of broad area application of contact insecticides used in mosquito control are becoming less effective, primarily due to resistance within mosquito populations. New methods that can deliver ingestible insecticides are being investigated as a means to mitigate resistance. This study evaluated insecticide delivery through toxic sugar baits (TSB) and resulting mortality of susceptible and resistant strains of Aedes aegypti. Two Ae. aegypti strains were evaluated using a 1% boric acid TSB: the susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Recent studies have also shown that ATSB can be used for the insecticide resistance management in mosquito vectors. [35][36][37][38] In an experimental hut trial of ATSB with LLIN in Côte d 0 Ivoire, addition of ATSB to LLIN increased the mortality of insecticide resistant An. gambiae significantly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have also shown that ATSB can be used for the insecticide resistance management in mosquito vectors. [35][36][37][38] In an experimental hut trial of ATSB with LLIN in Côte d 0 Ivoire, addition of ATSB to LLIN increased the mortality of insecticide resistant An. gambiae significantly.…”
Section: Discussionmentioning
confidence: 99%
“…37 Application of Bacillus thuringiensis israelensis (Bti) to ATSB provide an alternative approach for mosquito control. 37 Bti toxins do not engender resistance in mosquitoes despite prolonged use in contrast to chemical insecticides. Therefore, this could be a very practical and economical way for vector control in rural parts of India where sleeping under the nets is a cornerstone strategy for protection against bites and also where insecticide resistance among vector population is widespread.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations